Characterization of Cones and Seeds of Damar (Agathis labillardieri) from Plantation in Klasaman, Sorong - Jeffry Cornelis Angkotta; Julius Dwi Nugroho; Nurhaida Iriany Sinaga (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Damar (Agathis labillardieri) is endemic species to New Guinea, occurring naturally in Papua and West Papua Province, Indonesia. The species is economically valuable due to its resin and wood. This research aimed to study the cones and seeds characteristics of A. labillardieri collected from Sorong Nature Park at Klasaman, Sorong, Papua Barat. The characteristics observed included cone size and weight, number of scales, empty and filled seed, and seed moisture content. The germination test was also performed. Although the stands could produce cones, not all scales contained seeds, and not all seeds were filled seeds. On average, 53 filled seeds per cone or only 50.3 ± 5.7% of the total seeds found as filled seeds. The seed was characterized as a recalcitrant seed with high moisture content and rapid germination. On average, the seed moisture content was 38.9%, with an average germination time of four days. The combined factors that may contribute to the low natural regeneration of A. labillardieri are low filled seeds, seed sensitivity to desiccation, and high mortality in newly emerging seedlings during recruitment. Therefore, facilitating the forest floor for immediate germination of recalcitrant seeds as in A. labillardieri is suggested. Keywords: Agathis labillardieri, filled seed, germination, natural regeneration, recalcitrant seed